Davutoglu’s paradigm, Winkel’s epistemé and political science in Malaysia - Mohd Yusof, Danial (Brill, 2007)
Husserlian phenomenology and its terminology are utilised to justify the sociology of Islam and its essentialist response through the course of transcultural exchanges and sedimentation with the irreconcilable weltanshauung of the West. At the same time, the issue of structure and reliable knowledge is considered through the difficult relationship between revivalist religion and state politics where political legitimacy and the development of institutions is a feature of socio-political fact. Here, Malaysian political culture and democracy is used as an example. It makes out that sociopolitical realities, if not co-incidental with discourses of reliable knowledge and moral society, are representations of the conciliation of interests with specific value orientation with regards to alternative conceptions of moral society.